Implementation of Didactic Guide â€œThe Chemistry of Lifeâ€ Applying Hypermedia Resources for the Learning of Biochemistry - Bayas-MorejÃ³n, Isidro Favian (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The second level students from the Nursing School at the State University of Bolivar have been only using printed teaching material since 2013, so that they presented difficulties in the comprehension and learning of the biochemistry; the majority pupils did not manage contextualized and interrelate with clarity the thematic of the 14 didactic units of the subject and they limit themselves to memorizing the concepts. Objective and Method Used: The present research reveals the results obtained with the design and implementation of the guide â€œThe Chemistry of Lifeâ€ with the support of hypermedia tools to learn Biochemistry. For the development of the hypermedia application, it was used the program of visual author Multimedia Builder version 4.9.8., in system Windows Office and others softwareâ€™s for the audiovisual production. To that end, two groups of students were selected, a group control with whom in the teaching learning process of the biochemistry was used the traditional methodology and the experimental group, the guide, during 2014 academic period. Result and Discussion: The design applied was quasi experimental, to contrast the results themselves, that were submitted to a statistical, descriptive, and inferential analysis to showed, that with the use of the digital guide and the supported in the hypermedia application improved consistently the learning biochemistry and consistently in the studentâ€™s performance that belongs to experimental group in contrast to those of the control group. Therefore, the utilization of the guide is recommended and its complement, its structure comes added with information and communication technological, in hypertext format and multimedia, becoming it an educational technological innovative resource, which is characterized for being not linear and interactive, useful for the new generation and new forms of biochemistry learning and optimize the work in the classroom.